Realized niche shift associated with Galinsoga quadriradiata (Asteraceae) invasion in China. (2nd August 2021) - Zhang, Wengang; Chen, Xiaoyan; Liu, Ruiling; Song, Xingjiang; Liu, Gang; Zou, Jiabin; Qian, Zengqiang; Zhu, Zhihong; Cui, Langjun
Abstract: Shifts in the realized niches of exotic species may play an important role in their invasion. Galinsoga quadriradiata has invaded China widely and occupied many climate zones that are different from its native range. We addressed the climatic niche shift of G. quadriradiata and evaluated how this could contribute to its invasion in China. We used the Maxent model to predict the potential distribution of G. quadriradiata using its native and invaded range occurrences and climatic variables. Principal component analysis was conducted to measure climatic niche shifts of G. quadriradiata during its invasion in China. The models revealed only 32.7% niche overlap between the native and invasive populations. The niche similarity of the two populations was significantly low (Schoener's D = 0.093, P < 0.005), suggesting the occurrence of a niche shift. The envelop and center of the realized climatic niche in China has shifted to lower temperature and less precipitation compared to that in its native range. The majority of invaded areas in southern China are in the stabilizing zone, whereas the colonization and adaptation zones are predicted to be at the leading edge of G. quadriradiata invasion in northern China. This suggests that the regional distribution of G. quadriradiata may be in a quasi-equilibrium state, and that the species continues to invade environmentally suitable areas. Alterations in G. quadriradiata 's niche would help to explain why this species is so invasive in China.